Evaluation of a Set of Measures to Stimulate the Country’s Economy After the Exposure to the COVID-19 Virus: Lithuanian case - Giriuniene, Gintare; Giriunas, Lukas (The journal of contemporary issues in business and government, 2021)
In the wake of the economic changes brought about by the global COVID-19 pandemic, both states and organizations unifying them, have taken urgent action to mitigate the socio-economic impact and support economic recovery. Nevertheless, not all designed and implemented emergency measures have achieved the desired results. The purpose of the research is therefore to examine the effectiveness of these measures. Due to the limited amount of data, time period, and other conditions, only Pearson and Spearman correlation analysis was used to achieve the goal. Summarizing the results of the study, it can be stated that the biggest influence on the country's economy in the short term was the choice of measures to stimulate the country's economy after COVID-19 virus, rather than the restriction of movement or the number of COVID-19 patients. However, the wage subsidy used by most countries in the world has been identified as the best means of stabilizing the economy in the short term.